2022
DOI: 10.3390/f13010109
|View full text |Cite
|
Sign up to set email alerts
|

Soil Compaction after Increasing the Number of Wheeled Tractors Passes on Forest Soils in West Carpathians

Abstract: Soil disturbance and compaction are inherent in ground-based harvesting operations. These changes are affected by numerous factors, related mainly to the technical parameters of the machines, soil conditions, and the technology used. This study aimed to analyze the changes of surface layers of soil caused by skidder traffic without loads on the Cambisols of Western Carpathians. We observed changes in the soil bulk density and penetration resistance. The results showed that only machine traffic caused a 0.32 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…From the point of temporal development of rut depths after individual passes, we found that the rut depth after the first 5 passes represented 10% (UAT) to 49% (LKT) of the value after the 40th pass and did not stop increasing until the last measured pass. The values correspond with the changes in rut depths determined by [29] and with the changes in soil bulk density measured at the same plots [17], as well as with the values presented by [30]. Several authors [31,32] report the greatest damage after approximately the first 3-5 passes.…”
Section: Rutssupporting
confidence: 86%
See 1 more Smart Citation
“…From the point of temporal development of rut depths after individual passes, we found that the rut depth after the first 5 passes represented 10% (UAT) to 49% (LKT) of the value after the 40th pass and did not stop increasing until the last measured pass. The values correspond with the changes in rut depths determined by [29] and with the changes in soil bulk density measured at the same plots [17], as well as with the values presented by [30]. Several authors [31,32] report the greatest damage after approximately the first 3-5 passes.…”
Section: Rutssupporting
confidence: 86%
“…Basic data about the forest stand no. 544 extracted from the forest management plan and soil parameters[17].…”
mentioning
confidence: 99%
“…m-3 in the third pass, which emulates the RTF, noting form the figure that after the first pass, the Pb increased by (56%) compared with CTF, while after the second and third pass, it increased by (30%) and (16%) compared to zero traffic, , respectively. The reason for the increase in Pb is due to soil compaction which as result of wheel traffic, which is in close agreement with what was found by [23,24].…”
Section: Bulk Density (Pb)supporting
confidence: 91%
“…This is consistent with the results of Pb. The reason for this, is that passage of the tractor increases the soil compaction in the trace of the pass of tires (RTF), which increases the power requirement to complete the tillage process compared to ploughing the soil without compaction between the tractor tires (CTF), and this is consistent with what was found by [3,23,24]. it notes from Figure (4C) that the overlapping traffic system with tillage type had a significant effect (p < 0.05) on the DP, so that the ST with the first passage gave the lowest value of the DP (0.893) KW, while the DT with the second and third passage gave the highest value for the DP (4,340 and 4,272) KW, respectively, the reason for this is mentioned in the previous two paragraph Note: The difference in letters indicates that there is a significant difference between the treatments…”
Section: Drawbar Power (Dp)supporting
confidence: 79%
“…The samples were collected on the harvester tracks and forwarder trails at 2 m intervals. Ampoorter et al [31] and Allman et al [32] reported that the increase in the soil bulk density caused by forest machinery was confined to a depth of 0-20 cm of soil. A total of 3 transects with 90 samples were collected in the tracked harvester and 4 transects with 96 samples were collected in the wheeled harvester.…”
Section: Data Collectionmentioning
confidence: 99%